PERAN TUTOR SEBAGAI INISIATOR DALAM PRAKTIK PEMBELAJARAN KOMPETENSI BAHASA INGGRIS DI LEMBAGA KURSUS DAN PELATIHAN (LKP) LANTERN HOUSE BENGKULU - Laila Utyani Putri; Ririn Gusti; Wiwin Yunita (IKIP Siliwangi, 2026)
The purpose of this study is to describe the role of tutors as initiators in English learning at the LaternHouse Bengkulu Training and Course Institute (LKP). Data collection techniques were carried outthrough interviews, observation, and documentation. The results of the study indicate that tutors asinitiators have an important role in developing creative and innovative learning ideas and strategies.Tutors present various new ideas tailored to the learning material, such as the use of communicativemethods, educational games, and interactive activities such as card presentations, word puzzles, andword connection games. In addition, tutors also provide challenges and small projects to encouragecreativity and increase student activeness in the learning process.